A secure method to detect wormhole attack in mobile adhoc network - Ardestani, Parichehr Manouchehri (2013)
According to recent advances in wireless telecommunications, the performance and use of wireless technologies has increased extremely. In this study concerned on the Mobile Ad-hoc Network (MANET) is a collection of self-configuring mobile node without any infrastructure. There are different security flaws and attacks on the routing protocols in the MANET. One of the critical threats is the wormhole attacks, which have attracted a great deal of attention over the years. The wormhole attack can affect the performance of different routing protocols. During this attack, a malicious node captures packets from one location in the network, and “tunnels” them to another malicious node at a distant point, which replays them locally. This study presents a review of the most important solutions for counteracting wormhole attacks, as well as presents proposed method on DSR routing protocol for detecting them. The performance of the proposed method was examined through ns-2 simulations. Hence, the results show that proposed method can detect this serious attack in a Mobile Adhoc Network.